Salt tolerance research in date palm tree (Phoenix dactylifera L.), past, present, and future perspectives - Yaish, Mahmoud W.; Kumar, Prakash P. (Frontiers in plant science, 2015)
The date palm can adapt to extreme drought, to heat, and to relatively high levels of soil salinity. However, excessive amounts of salt due to irrigation with brackish water lead to a significant reduction in the productivity of the fruits as well as marked decrease in the viable numbers of the date palm trees. It is imperative that the nature of the existing salt-adaptation mechanism be understood in order to develop future date palm varieties that can tolerate excessive soil salinity. In this perspective article, several research strategies, obstacles, and precautions are discussed in light of recent advancements accomplished in this field and the properties of this species. In addition to a physiological characterization, we propose the use of a full range of OMICS technologies, coupled with reverse genetics approaches, aimed toward understanding the salt-adaption mechanism in the date palm. Information generated by these analyses should highlight transcriptional and posttranscriptional modifications controlling the salt-adaptation mechanisms. As an extremophile with a natural tolerance for a wide range of abiotic stresses, the date palm may represent a treasure trove of novel genetic resources for salinity tolerance.